Investigating the Hepatitis E seroprevalence rates among hemodialysis patients in Turkey with pool analyses method - Serpil Mızrakçı (Journal of Contemporary Medicine, 2022)
Objectives: Hepatitis E virus (HEV) is a worldwide public health problem that affects both poor and developed countries. Hemodialysis (HD) patients have been reported to be at risk for HEV infection due to the likelihood of parenteral and/or nosocomial transmission. The goal of this study was to analyze studies on HEV seroprevalence rates among hemodialysis patients and to highlight differences in disease seroprevalence between geographic regions. Material and Methods: Published literature in English and Turkish language (full text articles or detailed abstracts) on HEV seroprevalence among hemodialysis patients from Turkey were elavuated. Google Scholar, Pubmed, the Scopus, ULAKBIM TR Dizin and the Web of Science databases were scanned by using the keywords " hepatitis E virus " or " HEV " and " hemodialysis patient " or " hemodialysis " and " seroprevalence” or "IG G” and ‘’Turkey’’or "Turkish". The publications were assessed based on their general frequency, location, region and year. Results: The published literature on HEV seroprevalence among Turkish hemodialysis patients in both English and Turkish was reviewed. Only 11 articles were found according to the search criteria. Most of the studies (27.27%) were from the Southeast Anatolia Region. There were no studies from the Marmara and Eastern Anatolia regions. The regional seroprevalence of HEV among hemodialysis patients was highest in the Central Anatolia region (23.43%) and in the Southeastern Anatolia region (21.26%), and lowest in the Aegean region (5.95%). No studies were found in the literature search for the Marmara and Eastern Anatolia regions. Conclusion: The median of HEV seroprevalence rate was found as 17.62% in this study. The studies were limited, and it is necessary to increase the number of publications on HEV seroprevalence in risky groups from our country.